Mobility Aware Hybrid Medium Access Control protocols in Wireless Sensor Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Mobility of nodes in Wireless Sensor Networks brings many communication challenges like frequent topological changes, energy efficiency, collision rate and latency. To address these challenges, most of the researchers focused on Mobility aware Hybrid MAC protocol design to improve overall network performance which transforms between contention and schedule-based approaches. The techniques used in these protocols, adjust the duty cycle according to mobility of nodes and also use suitable mobility detection algorithms to handle mobility in an efficient manner. In this paper, mobility parameters, types, models and detection algorithms are discussed and provides a comprehensive study of mobility aware hybrid MAC protocols